Corona discharge characteristics of cylindrical electrodes in a two-stage electrostatic precipitator - Tsrong-Yi Wen; Jiann-Lin Su (Heliyon, 2020)
Electrostatic precipitator (ESP) is an electrohydrodynamic-based air filter that charges particles based on corona discharge and collects particles by induced electrostatic forces. Inducing corona discharge requires strong electric fields that, however, bring reliability issues because of oxidation. This paper presents the characteristics of an ESP that uses the cylindrical corona electrodes whose longitudinal axis is perpendicular to the surface of the ground electrode. The characteristics include the current-voltage curve, the surface oxidation of the cylindrical corona electrodes, and the element analysis. The characteristics are presented with respect to the pitch and diameter of the cylindrical corona electrodes. The results show that the characteristics mentioned above can correlate to the electric fields around the cylindrical corona electrodes. Stronger electric field around the cylindrical corona electrode results in higher collection efficiency, more oxidation on the cylindrical corona electrode, and shorter life of the cylindrical corona electrode.